TO THE PROBLEM OF EVALUATION OF EDUCATIONAL ACHIEVEMENTS PUPILS OF SPECIALIZED CLASSES IN LAW - Maiorskyi, Viacheslav V. (Educological discourse, 2015)
The article is devoted to selected aspects of evaluation of educational achievements of pupils of profile classes public humanities direction in Law. It identifies the main problems in the evaluation of pupils of profile classes – the lack of developed evaluation criteria, the subjectivity in the evaluation, the lack of experience of teachers in the use of various forms and procedures of evaluation. It focuses on the functions, objectives, the character and the objects of evaluation. It expounds approaches to evaluation, steps and peculiarities of procedures of evaluation of educational achievements of pupils in Law. It describes the technology of testing, with justification.